PENGELOMPOKAN KABUPATEN/KOTA DI JAWA TENGAH BERDASARKAN KARAKTERISTIK KESEJAHTERAAN RAKYAT MENGGUNAKAN METODE WARD’S - Shofa Kartikawati; Atika Nurani Ambarwati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The welfare of the people is a condition in which a citizen can fulfill and sufficiently fulfill the needs of his life, both material and spiritual. The welfareof the people is one of the goals of the Unitary State of the Republic ofIndonesia which is established in the preamble of the 1945 Constitution.Central Java Province in 2015 is included in the 5 provinces with the largestpopulation in Indonesia with a population growth of 0.15 percent compared to2014. As for the population density reached 1038 inhabitants / km2. With thesecond poorest in Indonesia. The purpose of this paper is to know the groups ofdistricts / municipalities in Central Java based on the characteristics of people'swelfare and characteristics of each group of districts / cities based on thecharacteristics of people's welfare. The data analyzed is data taken from theCentral Statistics Agency (BPS) of Central Java Province in 2015. Variablesused are Poor People, Human Development Index, Open Unemployment Rate,Infant Mortality Rate, District / City Minimum Wage, Population Density andGRDP Per Capita. The method used is hierarchy method, agglomerativetechnique and distance measure Euclidean distance. Based on the results of theanalysis can be concluded that the district / city in Central Java can be groupedinto 3 clusters. Cluster 1 consists of 16 districts and 1 city with medium welfarelevel, cluster 2 consists of 12 districts that have low level of people's welfare,cluster 3 consists of 1 regency and 5 cities with high people welfare level. Kata kunci:  Cluster Analysis, People Welfare, Ward’s.